Prediction of Creep Concrete in Lightweight Concrete with Pumice as Coarse Aggregate - Maulidyah, Chairah; Wisnumurti; Desy Setyowulan (Rekayasa Sipil, 2024)
Concrete creep is the additional strain that develops in concrete under constant stress over time. In this study, lightweight concrete is created by entirely replacing coarse aggregate with pumice to reduce the concrete's overall weight. The research involves producing 18 cylindrical concrete test specimens with a diameter of 150mm and a height of 300mm. These specimens include three normal and three lightweight concrete samples for each 90-day creep test and three normal and three lightweight concrete samples for compressive strength tests on the 14th and 28th days. The variation in aggregate proportions affects the aggregate content and weight in each type of concrete, influencing their properties. This is evident in the creep curves for the lightweight concrete samples. Similarly, the differences in the creep curves for normal concrete samples are attributed to stress distribution during loading. The strain acceleration between normal and lightweight concrete under load remains similar until the final loading day at 90 days. However, lightweight concrete significantly increases creep value after prolonged loading, rising by 35.85%. In contrast, normal concrete exhibits a creep increase of 16.51% from the beginning of loading until the 90th day.